Whale optimisation algorithm tuned fractional order PIλDμ controller for load frequency control of multi-source power system. (3rd June 2019) - Kumar, Amit; Suhag, Sathans
This paper deals with the design and optimisation of a fractional order PI λ D μ (FOPID) controller implemented for load frequency control (LFC) of a multi-area multi-source power system having the nonlinearities of time delays, generation rate constraint (GRC) and governor dead band (GDB). Whale optimisation algorithm (WOA), arguably for the first time in this area, is applied for optimal tuning of the parameters of FOPID controller. The comparative analysis of the performance of WOA vis-à-vis other recent evolutionary optimisation approaches is carried out from which it is observed that WOA optimised FOPID controller gives the best dynamic performance in terms of settling time and maximum overshoot in frequency and tie-line power deviations. Further, investigations carried out against system parametric variations within the range of ± 25% reveal that WOA tuned FOPID controller is the most effective and robust against wide variations in system parameters.